1997
DOI: 10.1037/h0080258
|View full text |Cite
|
Sign up to set email alerts
|

Process and outcome in a hostel outreach program for homeless clients with severe mental illness.

Abstract: A longitudinal study followed 55 homeless and severely mentally ill clients of a hostel outreach program to assess outcomes and their relationship to program elements. Results at 18-month follow-up indicated that, despite chronic histories of transiency and shelter use, housing stability had been achieved, and that initial gains in social functioning and symptom reduction had been increased. Development of a strong working alliance proved a key program element in the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 31 publications
2
45
0
1
Order By: Relevance
“…In 6 studies, a total of 10 associations between the TR and symptom levels as outcomes of subsequent treatment were reported [14,17,19,21,22]. With respect to the symptom scales used in the studies, we distinguished between observer-rated [14,17,19] and patient-rated measures [19,21,22].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 6 studies, a total of 10 associations between the TR and symptom levels as outcomes of subsequent treatment were reported [14,17,19,21,22]. With respect to the symptom scales used in the studies, we distinguished between observer-rated [14,17,19] and patient-rated measures [19,21,22].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 2 associations were from the same 2 studies and non-significant. In 1 study [17] a non-significant association was reported in a model that also included baseline symptom scores and weeks in permanent residence as predictors. Five associations were reported between the TR and patient-rated symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations